2000
DOI: 10.1161/01.cir.102.5.572
|View full text |Cite
|
Sign up to set email alerts
|

Fas-Mediated Apoptosis in Adriamycin-Induced Cardiomyopathy in Rats

Abstract: Background —The precise molecular mechanism of Adriamycin-induced cardiomyopathy (ADR-CM) is still unknown. We address the demonstration of apoptotic myocardial cell death and the apoptosis-inducing molecules in ADR-CM induced in rats. Methods and Results —Until 8 weeks after the first administration of ADR, there was no increase in the number of labeled cells by terminal deoxynucleotidyl transferase assay (TUNEL method). Apoptotic indices increased sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
120
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(140 citation statements)
references
References 31 publications
14
120
0
2
Order By: Relevance
“…Altogether, this indicates the involvement of caspase-independent apoptotic routes in mediating death in cardiac myocytes by DOX. This cannot be generalised because in other cell types (in our study and in previous reports) caspases seem to play a role in DOX-induced cell death (Nakamura et al, 2000;Grassilli et al, 2004;Kalivendi et al, 2005). Together this supports the idea that more than one mechanism can mediate programmed cell death, which depends on both the death stimulus provided and the cell type studied (Bröker et al, 2005).…”
Section: Discussionsupporting
confidence: 63%
“…Altogether, this indicates the involvement of caspase-independent apoptotic routes in mediating death in cardiac myocytes by DOX. This cannot be generalised because in other cell types (in our study and in previous reports) caspases seem to play a role in DOX-induced cell death (Nakamura et al, 2000;Grassilli et al, 2004;Kalivendi et al, 2005). Together this supports the idea that more than one mechanism can mediate programmed cell death, which depends on both the death stimulus provided and the cell type studied (Bröker et al, 2005).…”
Section: Discussionsupporting
confidence: 63%
“…ADR caused decreased blood pressure (MBP, SBP, and DBP); this was probably responsible for the decreased LV function due to a decreasd ratio of LV to body weight. The decline of LV weight may be explained by myofibrillar loss associated with inducion of apoptosis and due to the inhibition of the expression of some genes specific for cardiac muscles, such as a-actin, troponin by ADR (Boucek et al 1999;Nakamura et al 2000). The compensation mechanism e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that numerous signaling molecules, such as cytochrome c, Bcl-2, Bax, p53, and Fas, have been implicated in the apoptotic pathways of cardiomyocytes [15,16] . Bcl-2 family members include Bax, Bcl-2, and Bcl-xl.…”
Section: Discussionmentioning
confidence: 99%